2018
DOI: 10.1039/c8md00237a
|View full text |Cite|
|
Sign up to set email alerts
|

Design, synthesis, and evaluation of bitopic arylpiperazine-phthalimides as selective dopamine D3 receptor agonists

Abstract: The dopamine D3 receptor (D3R) is a proven therapeutic target for the treatment of neurological and neuropsychiatric disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…In more cases, dualsteric modulators are designed by combining the orthosteric and allosteric ligand with a linker. 50,56,57,59,62,63,65,66,69,70,73,75,77–86,88,89,91,92,96,97,99,100,102–104,106–109,111,114–118,120–123,126,127,132,133,136,138,140,143,145,148–150,153,154,156,160,161,163,165,166,169,170,178–182,185,186,188,195,228 This is similar with the fragment-based drug discovery (FBDD). 229 The core fragments of drug binding is first identified and then the fragments are grown, merged, or linked into one complete molecule.…”
Section: Design Of Dualsteric Modulatorsmentioning
confidence: 73%
See 3 more Smart Citations
“…In more cases, dualsteric modulators are designed by combining the orthosteric and allosteric ligand with a linker. 50,56,57,59,62,63,65,66,69,70,73,75,77–86,88,89,91,92,96,97,99,100,102–104,106–109,111,114–118,120–123,126,127,132,133,136,138,140,143,145,148–150,153,154,156,160,161,163,165,166,169,170,178–182,185,186,188,195,228 This is similar with the fragment-based drug discovery (FBDD). 229 The core fragments of drug binding is first identified and then the fragments are grown, merged, or linked into one complete molecule.…”
Section: Design Of Dualsteric Modulatorsmentioning
confidence: 73%
“…After a manual filtering, 133 research articles focusing on identifications of novel dualsteric modulators were found. Modulators targeting GPCR 50,53,56–137 or kinase 138–157 account for more than three quarters (Fig. 5).…”
Section: Targets For Dualsteric Modulatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The approach was validated by the synthesis and experimental evaluation of the designed compounds. Classical docking and virtual screening approaches could be also utilized for the development of bitopic compounds ( Cao et al, 2018 ) and even to develop fluorescent GPCR probes ( Prokop et al, 2021 ). We highlight here a study that utilized structure guided design of GPCR polypharmacology ( Kampen et al, 2021 ).…”
Section: Design Approaches For Allosteric and Bitopic Compoundsmentioning
confidence: 99%